Mobile computing in patient relationship management - A case study - Moreira, Pedro (2018)
Around fourteen years ago, the first hospital in Portugal started to use a patient notification system, to alert patients of their medical events at the hospital, such as appointments, surgeries, exams, treatments through text messages. This notification system is used nowadays, but it faces a big problem: a huge amount of money spent for the telecommunication companies involved. Although each message cost a fraction of cents, it can easily reproduce its value in more than 50,000 euros per year per institution. Since technology and the use of smartphones has been evolving in such a quick way, it is estimated that in no more than 10 years, almost all the Portuguese population will use smartphones or have access to them. For those reasons, the main purpose of the present work, is to design and develop a mobile application in order to substitute the previous notification systems, through push up notifications on the app and by email, that can be saved on the smartphone calendar, translating in no costs associated with the notifications sent by the hospitals. The main motivation is, therefore, suppressing these costs for the hospital, bring the patients closer integrating other systems on the app and make the notification alert more efficient. Thereby, the mobile app will be able, not only to manage each notification and notify the patients, but also to check its medical event history and to schedule medical appointments.